Most common musculoeskeletal injuries in profesional volleybal players. - Carrasco-De-La-Fuente, María del Carmen; Alabau-Dasi, Raquel (My University, 2024)
Volleyball is a complex discipline with high technical tactical and athletic demands on the players. Serving, passing and setting the ball are accompanied with spiking or attacking actions. Starting with an approach followed by a vertical jump, one of the objectives of the volleyball spike is to hit the ball at the highest possible speed. A highly skilled attacker with 16 to 20 hours of weekly practice time spikes for example about 40000 times a year. Considering the various technical requirements and the popularity of the sport, studies have studied injury incidence and indicated that they are quite frequent. The injury incidence is between 1.7 and 4.2 per 1000 hours of play and it is the fourth most common source of sports injuries. Despite the large number of studies for injury incidence in volleyball and factors related to them there is a gap concerning the influence of expertise level – professional players or not – in injury rate related to all the factors mentioned, such as type, severity, anatomical location of injuries, if they occurred during practice or game or during competitive or pre or postseason.
Most frequent injuries in volleyball players. A descriptive study.
Keywords: Voleibol - Lesiones y heridas; Volleyball; Injuries